Clinical significance of matrix metalloproteinase 9 and tissue inhibitor of metalloproteinase 1 and 2 in Kawasaki disease - Ki Wook Yun; Sin Weon Sin; Jung Ju Lee; Soo Ahn Chae; In Seok Lim; Eung Sang Choi; Byoung Hoon Yoo; Mi-Kyung Lee (Korean Pediatric Society, 2010)
Purpose : Kawasaki disease (KD) is a systemic vasculitis, a leading cause of pediatric acquired heart disease. Histopathological findings of coronary artery lesion (CAL) in KD indicate destruction of the coronary artery wall with diffuse vasculitis. Matrix metalloproteinases (MMPs) and their endogenous tissue inhibitors (TIMPs) might play central roles in this process. Special attention to MMP-9 has recently been emerging. This study was performed to investigate the clinical significance of MMP-9 and its inhibitors, TIMP-1 and TIMP-2, in KD. Methods : We compared 47 KD patients with 14 febrile controls. Serum MMP-9 and TIMP-1, TIMP-2 were measured by ELISA and compared according to clinical stages and coronary involvement. Results : In acute stage, MMP-9 and TIMP-1 were significantly higher, whereas TIMP-2 was lower, in KD than those in febrile controls (P <0.05). The elevated MMP-9 levels in acute phase significantly decreased during the subacute and convalescent phases (P <0.05). During acute phase, the MMP-9, TIMP-1, and MMP-9/TIMP-2 levels in the CAL group were lower than those in the non-CAL group, but they increased significantly in the subacute phase (P <0.05). MMP-9 has a positive correlation with TIMP-1 in the acute and subacute phases, and negative correlation with TIMP-2 in the subacute and convalescent phases (P <0.05). Conclusion : These results suggest that MMP-9, TIMP-1, and the imbalance in MMP-9 and TIMP-2 might play important roles on the pathophysiology of KD and especially on the development of CAL. However, further larger studies are needed.